Ionospheric response to AGW propagation detected using GNSS measurements and coherent sounding over “Vernadsky” and “Palmer” Antarctic stations - Sopin, A. A.; Yampolski, Yu. M.; Paznukhov, V. V.; Kascheev, S. B.; Koloskov, A. V.; Pikulik, I. I.; Zalizovski, A. V.; Kashcheyev, A. S. (Ukrainian Antarctic Journal, 2016)
The work presents results of the diagnostics of travelling ionospheric disturbances (TIDs) over the Antarctic Peninsula obtained by using two different techniques. The first method is based on ground-based multi- positional GNSS TEC measurements, and the second one is bistatic coherent ionospheric HF radio sounding between “Akademik Vernadsky” and “Palmer” Antarctic stations. A comparison of Doppler frequency shifts of the probe HF signal received at “Palmer” station with the dynamics of TEC variations has been made. Quasi-periodic variations associated with the propagation of TIDs were registered simultaneously in both types of the data. A case study performed in this paper has shown that the parameters of the ionospheric disturbance estimated by two methods are in a good agreement, given a specific choice of ionospheric pierce point (IPP) trajectories of GNSS links near the reflection point of the HF probing signal and TID motion direction collinear to the radiopath and perpendicular to IPP trajectories.